Sikap mahasiswa Program Studi Sarjana Kedokteran dan Profesi Dokter angkatan 2016 Fakultas Kedokteran Universitas Udayana terhadap peran media sosial sebagai alternatif small group discussion secara online - Ida Bagus Made Mahendra Wisma; Putu Ayu Asri Damayanti; Ni Putu Wardani (DiscoverSys Inc., 2020)
Background: The rapid development of information and communication technology provides an alternative in disseminating knowledge, especially accessing information in the field of education. Increasing access to information through social media can develop cognitive power in student groups, such as through discussion learning methods based on Small Group Discuccion (SGD) at the Faculty of Medicine, Udayana University.Aim: To evaluate the attitude of students batch 2016 Medical Faculty and Doctor Professional Study Program (PSSKPD) Faculty of Medicine of Udayana University towards the role of social media as an alternative to online SGDMethod: This study was an observational study using a cross sectional descriptive design of the batch 2016 PSSKPD students of the Faculty of Medicine, Udayana University in the period August-November 2019.Result and Conclusion: The most commonly used social media by PSSKPD students batch 2016 at the Faculty of Medicine of Udayana University in carrying out SGD was social media LINE (83.5%). The description related to knowledge about the role and benefits of social media is 84.4%. The description of students' attitude towards social media-based SGD has a high positive value of 97.9%. The description of students' attitudes towards the amount of information obtained through SGD based on social media namely 89.6% agreed and 20.8% strongly agreed. The role of social media as an alternative to SGD online greatly helps students learn. understanding the topic of discussion as well as interacting, arguing, and add insights.Â Â Latar Belakang: Perkembangan teknologi informasi dan komunikasi yang sangat pesat memberikan alternatif dalam menyebarluaskan ilmu pengetahuan terutama mengakses informasi dalam bidang pendidikan. Peningkatan akses informasi melalui media sosial dapat mengembangan daya kognitif pada kelompok pelajar, seperti melalui metode pembelajaran diskusi berbasis Small Group Discuccion (SGD) di Fakultas Kedokteran Universitas Udayana.Tujuan: Untuk mengetahui sikap mahasiswa Program Studi Sarjana Kedokteran dan Profesi Dokter (PSSKPD) angkatan 2016 Fakultas Kedokteran Universitas Udayana terhadap peran media sosial sebagai alternatif SGD secara online Metode: Penelitian ini merupakan penelitian observasional yang menggunakan rancangan deskriptif cross sectional terhadap mahasiswa PSSKPD angkatan 2016 Fakultas Kedokteran Universitas Udayana periode Agustus-November 2019.Hasil dan Simpulan: Media sosial yang paling sering digunakan oleh mahasiswa PSSKPD angkatan 2016 Fakultas Kedokteran Universitas Udayana dalam melaksanakan SGD adalah media sosial LINE (83,5%). Gambaran terkait pengetahuan mengenai peran dan manfaat media sosial adalah sebesar 84,4%. Gambaran sikap pernyataan mahasiswa terhadap SGD berbasis media sosial memiliki nilai positif yang tinggi sebesar 97,9%. Gambaran sikap mahasiswa terhadap besarnya informasi yang didapatkan melalui SGD berbasis media sosial yakni 89,6% menyatakan setuju dan 20,8% sangat setuju. Peran media sosial sebagai alternatif SGD online sangat membantu mahasiswa belajar. memahami topik diskusi serta, berinteraksi, berargumentasi, serta saling menambah wawasan.Â